2017
DOI: 10.1111/bpa.12516
|View full text |Cite
|
Sign up to set email alerts
|

Axonal loss in the multiple sclerosis spinal cord revisited

Abstract: Preventing chronic disease deterioration is an unmet need in people with multiple sclerosis, where axonal loss is considered a key substrate of disability. Clinically, chronic multiple sclerosis often presents as progressive myelopathy. Spinal cord cross-sectional area (CSA) assessed using MRI predicts increasing disability and has, by inference, been proposed as an indirect index of axonal degeneration. However, the association between CSA and axonal loss, and their correlation with demyelination, have never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 58 publications
6
58
0
Order By: Relevance
“…Significant axonal loss takes place in the MS spinal cord, degree of which appears most strongly associated with the duration of the disease. A recent study reported reduction of axonal density in the cortico‐spinal tracts by 57%–62% across all cord levels after a mean disease duration of 29 years , confirming earlier studies using tissue from pwMS with similar disease duration , while studies of material with shorter disease duration reported less pronounced axonal loss . In line with this observation, axonal loss [be it within or beyond the margins of MS lesions ] is considered a major contributor to the relentless accrual of disability in pwMS over time.…”
Section: Axonal Loss In Lesions and Beyondsupporting
confidence: 67%
See 2 more Smart Citations
“…Significant axonal loss takes place in the MS spinal cord, degree of which appears most strongly associated with the duration of the disease. A recent study reported reduction of axonal density in the cortico‐spinal tracts by 57%–62% across all cord levels after a mean disease duration of 29 years , confirming earlier studies using tissue from pwMS with similar disease duration , while studies of material with shorter disease duration reported less pronounced axonal loss . In line with this observation, axonal loss [be it within or beyond the margins of MS lesions ] is considered a major contributor to the relentless accrual of disability in pwMS over time.…”
Section: Axonal Loss In Lesions and Beyondsupporting
confidence: 67%
“…However, compared to controls axonal density was reduced by 57%-62%. And while disease duration was a predictor of reduced axonal density, CSA was not, and neither were separate indices of proportional gray or white matter area (55).…”
Section: Spinal Cord Cross-sectional Area As a Proxy Of Axonal Loss?mentioning
confidence: 86%
See 1 more Smart Citation
“…The lack of correlation in chronic MS between neocortical demyelination and neuronal loss is also strikingly similar to the lack of such association between the total amount of demyelination and axonal loss in the chronic MS spinal cord . It will be of interest to investigate these relationships using post mortem tissue of the entire neuraxis, which to our knowledge has only been performed once in a relatively limited sample .…”
Section: Discussionmentioning
confidence: 68%
“…The comparative pathology studies demonstrate that, similar to the brain, MS spinal cord is affected by focal demyelination in white and grey matter, microglial proliferation, macrophage and T cell infiltration, astrogliosis, axon degeneration and neuronal loss [11][12][13][14][15][16]. In MS spinal cord, the extent of white as well as grey matter demyelination is high compared to brain regions [17].…”
Section: Introductionmentioning
confidence: 99%